Monitoring Small-Scale Cross Border Trade in Africa : Issues, Approaches, and Lessons - World Bank (World Bank, Washington, DC, 2020)
This report synthesizes the work carried out as part of a World Bank ASA (Advisory Services and Analytics) activity to identify better systems and practical strategies that countries can use for improved monitoring of small-scale cross border trade (SSCBT). Large amounts of goods are known to be traded through cross border channels in Africa, yet SSCBT is poorly counted leading to a misrepresentation of the true state of regional integration and possible misalignment of trade and development policies. The study assesses the strengths and limitations of existing SSCBT data systems in East Africa to understand the feasibility and cost effectiveness of different data collection methods. It also looks at conditions along trade corridors in other regions of Africa where SSCBT data are only starting to be monitored to identify common bottlenecks and potential solutions for improved trade data collection in different environments. The analysis draws on fieldwork carried out during July and August 2019, as well as subsequent consultations with local counterparts, including with respect to the impact of the COVID-19 pandemic. Through this work, the study aims to inform policy in countries where SSCBT is important and where the establishment of monitoring systems will be relevant and desirable. The project also contributes to discussions and negotiations on regional integration by raising the profile of SSCBT and drawing attention to the importance of addressing barriers that limit this trade. In addition to this report, findings of the ASA are also being shared with a diverse audience of policymakers, economic analysts, and civil society representatives through short policy notes, working papers, and dissemination events.